STRATEGY AND IMPLEMENTATION OF CHARACTER EDUCATIONIN ERA OF SOCIETY 5.0 - Wardani; Mayang Sari; Akmaluddin; Kaulan Kariman (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This article describes the importance of building character in the 5.0 society era. Era 5.0 society is a conception of a society that is literate towards Information and Communication Technology (ICT). Strengthening character education also needs to be realized, this is aimed at shaping character traits (manners) that make morals a distinctive value. The purpose of this study was to determine the strategies and ways of implementing character education in students. In addition, this study also aims to explain how ideal character education is in the face of the 5.0 society era